The Palestine–Israel Conflict and the Role of the European Union: Historical Context, Policy Dynamics, and Prospects for a Just Peace - Humaira Saeed; Faisal Charan; Rameez Haider (Journal of Religion and Society, 2026)
This article interrogates the Palestine–Israel conflict through a multidimensional analytical framework integrating historical institutionalism, international legal norms, and EU foreign policy behavior as conceptualized within the literature on normative power and external governance. By situating the conflict within a longue durée trajectory of settler-colonial dynamics, territorial fragmentation, and asymmetric power relations, the study elucidates how structural conditions embedded since the Mandate period continue to shape contemporary governance modalities, security regimes, and displacement patterns. The analysis foregrounds the European Union’s role as a composite international actor whose policies are mediated by internal preference heterogeneity, institutional path dependencies, and the constraints of a consensus-based Common Foreign and Security Policy (CFSP) architecture. Empirically, the article synthesizes EU diplomatic outputs, legal positions on occupation and settlement activity, aid disbursement patterns, and engagement within multilateral for a including the Quartet to assess the extent to which the EU functions as an effective norm entrepreneur or predominantly as a technocratic stabilizer within an entrenched conflict system. The findings suggest that while the EU exerts significant structural influence through financial governance mechanisms, regulatory differentiation, and human rights monitoring, its transformative impact is attenuated by exogenous power asymmetries most notably U.S. dominance in mediation and endogenous constraints on deploying coercive conditionality. The article concludes that enhancing EU efficacy requires a recalibration toward a rights-based, enforceable, and internally coherent strategy that operationalizes international humanitarian and human rights law not merely as discursive resources but as actionable policy instruments. Keywords: Palestine–Israel Conflict, European Union Foreign Policy, Occupation and Settlements, Multilateral Diplomacy